The Role of Webqual 4.0: Shopee User Satisfaction in Munjungan District - Prasetyo, Muhammad Riyan; Muslih, Basthoumi (Universitas Nusantara PGRI Kediri, 2024)
Research aim: The purpose of this study is t evaluate Shopee web users satisfaction in Munjungan District, Trenggalek Regency, East Java, using WebQual 4.0. Design/Method/Approach: The approach in this study uses a causal quantitative approach with the population, namely Shopee application users in Munjungan District who have made purchases. This study, which uses simple random sampling as a sampling technique, has 160 respondents based on the theory of Hair et al. Data collection used in the form of instruments through distributing questionnaires. In this research data analysis using instrument test technique, classical assumption tests, and multiple linear regression tests through the SPSS application. Research Finding: The findings in the study indicate that WebQual 4.0 has a significant influence on Shopee web user satisfaction in Munjungan District, Trenggalek Regency, East Java. Theoritical contribution/Originality: This research has contributed to the understanding and insight into usability, information quality, service interaction, and user satisfaction during purchases. Practical/Policy Implication: The implications obtained from this research are for companies to gain an improved user experience, increase customer retention, and strengthen brand image. Meanwhile,consumers get benefits such a easier navigation, a more responsive interface, better product filtering, and a pleasant experience during online shopping. Research limitation: This study has limitations such as the insufficient of respondents, which targets 160 respondents but gets 102 people. This happened because some respondent were reluctant to complete the online form and there was a limit for filling it out.